2022
DOI: 10.1186/s12951-022-01554-y
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin- and resveratrol-co-loaded nanoparticles in synergistic treatment of hepatocellular carcinoma

Abstract: Background Currently, systemic therapies for patients with advanced-stage hepatocellular carcinoma (HCC) rely mainly on systemic drugs. However, traditional systemic drugs have a high rate of serious adverse events, and the curative effects of some potential anticancer drugs, such as curcumin (CUR) and resveratrol (RSV), are less apparent due to their poor bioavailability. Therefore, it is urgent to develop a highly effective therapy to improve patient prognosis. Herein, an injectable HCC-targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…Furthermore, it was proposed that these nanoparticles induce apoptosis in cancer cells by generating ROS and activating caspase 3 in vivo. 89 A different study involved the development of delivery systems using solid lipid nanoparticles loaded with curcumin-resveratrol. These SLNs exhibited small mean diameters of 180.17 ± 7.69 nm and possessed a Zeta potential value exceeding −30 mV.…”
Section: Resveratrolmentioning
confidence: 99%
“…Furthermore, it was proposed that these nanoparticles induce apoptosis in cancer cells by generating ROS and activating caspase 3 in vivo. 89 A different study involved the development of delivery systems using solid lipid nanoparticles loaded with curcumin-resveratrol. These SLNs exhibited small mean diameters of 180.17 ± 7.69 nm and possessed a Zeta potential value exceeding −30 mV.…”
Section: Resveratrolmentioning
confidence: 99%
“…Another antitumor agent currently used in cancer therapy is curcumin, which stimulates apoptosis and cell cycle arrest, impairs metastasis, and increases chemosensitivity [ 203 205 ]. In HCC, curcumin impairs tumor cell progression by affecting molecular signaling pathways, and its efficacy can be enhanced by nanoparticle delivery [ 206 208 ]. Trichloroethylene can induce EMT to promote HCC cell progression and metastasis.…”
Section: Pharmacological Regulation Of Stat3 In Hccmentioning
confidence: 99%
“…In another recent study related to nanoformulation, hepatocellular carcinoma‐targeted nanoparticles with curcumin and resveratrol were designated for improving the phytochemical properties of hepatocellular carcinoma. These polymeric nanoparticles led to a considerable reduction in the phytochemicals dosage, sustained phytochemicals release, enhanced the bioavailability of the loaded phytochemicals, and increased the concentration of the phytochemicals at the tumor target site (Zheng et al, 2022). Recently, Kou et al have shown that compound of curcumin and resveratrol in nanosized dimension indicated synergistic anticancer efficacy on colon cancer by inducing cell cycle arrest, necrosis, and apoptosis in vitro and in vivo.…”
Section: The Anticancer Efficacy Of Single Polyphenols Plus Their Com...mentioning
confidence: 99%